The Role of Guidance and Counseling in Non-Formal Education in Indonesia - Melva Syahrial; Yeni Karneli; Ifdil; Netrawati (Manajia: Journal of Education and Management, 2025)
Education is an important human right to be accessed by everyone without exception. One form of education in Indonesia is non-formal education. Non-formal education is one of the main pillars in nation development. Non-formal education in Indonesia also continues to develop and adapt to changing times. Non-formal education is very much needed. In Indonesia, there are various non-formal education programs that can help students who cannot afford to get an education and improve their skills to achieve it. For students who have to help their parents, non-formal education can be the right alternative to continue to receive education and improve their skills, while also helping to ease the burden on their parents. The government is trying to fulfill the right to education for all Indonesian children, including students who are far from access to education. The right to education is a shared responsibility. Various efforts have been made by the government and various parties to provide quality non-formal education for children in remote and outermost areas so they can have an education. Students in non-formal education have diverse needs. They may come from various backgrounds in age, education and life experience. Counseling can help them adjust to new learning environments and overcome specific learning obstacles.